The lexico-structural/semantic progression in discourse topic construction: evidence from commento articles - Alonso, Pilar (Círculo de Lingüística Aplicada a la Comunicación, 2013)
In this article, Seuren’s notion of mod-proposition is taken as point of departure to address the question of discourse topic. Seuren distinguishes between the classic notion of proposition (flat-propositions) and modulated propositions (mod-propositions), and assigns to the latter a topic-comment modulated structure which becomes essential to decide on the information structure of discourse, especially in terms of incrementation. Drawing from this propositional modulated status, different theoretical approaches to the notion of topic at sentence level are reviewed and special attention is paid to the syntactic functions identified by these theoreticians as predominantly topical. Then the empirical analysis of a small corpus of comment articles in English is used to classify the linguistic strategies employed in the construction of a global discourse topic; this procedure makes it possible to focus on those topics which gradually acquire global projection by re-use, in opposition to those pieces of information which are topical only at the local level. Based on this evidence, our research shows the linguistic mechanisms which allow for re-used topical information to gradually acquire subject status as discourse progresses and proposes thinking in terms of intermediate information structures as subsumers of local information and builders of global topics.